Gaps in Understanding Mechanism and Lack of Treatments: Potential Use of a Nonhuman Primate Model of Oxaliplatin-Induced Neuropathic Pain. (2nd May 2018) - Hama, Aldric; Natsume, Takahiro; Ogawa, Shin'ya; Higo, Noriyuki; Hayashi, Ikuo; Takamatsu, Hiroyuki
Abstract : The antineoplastic agent oxaliplatin induces an acute hypersensitivity evoked by cold that has been suggested to be due to sensitized central and peripheral neurons. Rodent-based preclinical studies have suggested numerous treatments for the alleviation of oxaliplatin-induced neuropathic pain, but few have demonstrated robust clinical efficacy. One issue is that current understanding of the pathophysiology of oxaliplatin-induced neuropathic pain is primarily based on rodent models, which might not entirely recapitulate the clinical pathophysiology. In addition, there is currently no objective physiological marker for pain that could be utilized to objectively indicate treatment efficacy. Nonhuman primates are phylogenetically and neuroanatomically similar to humans; thus, disease mechanism in nonhuman primates could reflect that of clinical oxaliplatin-induced neuropathy. Cold-activated pain-related brain areas in oxaliplatin-treated macaques were attenuated with duloxetine, the only drug that has demonstrated clinical efficacy for chemotherapy-induced neuropathic pain. By contrast, drugs that have not demonstrated clinical efficacy in oxaliplatin-induced neuropathic pain did not reduce brain activation. Thus, a nonhuman primate model could greatly enhance understanding of clinical pathophysiology beyond what has been obtained with rodent models and, furthermore, brain activation could serve as an objective marker of pain and therapeutic efficacy.